Printing the Levellers: Clandestine Print, Radical Propaganda, and the New Model Army. (2nd December 2021) - Como, David R
Abstract: this article uses techniques of typographical analysis to identify the print houses that secretly produced the most important writings associated with the incipient 'Leveller' grouping as it took shape in 1646–47. It examines the key printers, Jane Coe and Thomas Paine, while illuminating the dynamics of the clandestine book trade of the 1640s. It then shows that these same printers acted as stationers of choice for the emergent New Model Army agitators, producing works such as the The Case of the Army Truly Stated and An Agreement of the People, among other titles. The resulting account sheds light on the origins and nature of the Leveller movement, and allows for discussion of the connections between the Levellers and the New Model Army. More broadly, this article highlights the centrality of printers as political protagonists and suggests that new modes of bibliographical analysis can address major problems in early-modern history.